PREVALENCE AND CAUSES OF TRANSITORY LOSS OF CONSCIOUSNESS IN GENERAL POPULATION (BY THE DATA FROM ЭССЕ-RF TRIAL) - S. A. Gudkova; N. A. Cherepanova; G. A. Golovina; D. V. Duplyakov; S. M. Khokhlunov; O. M. Rotar; A. O. Konradi; E. V. Schlyakhto (Российский кардиологический журнал)
Aim. To study prevalence of transitory loss of consciousness (TLC) in general population of the city Samara and to suggest its genesis according to anamnestic data.Material and methods. The material for the study was provided by a simple randomized selection of persons from general population in Samara city, performed during the multicentre observational trial "Epidemiology of Cardio-Vascular Diseases in the Regions of Russian Federation — ЭССЕ-RF". Total volume of the selection was 1796 persons (more than 80% responded to the call). Average age of the studied persons was 45,8±11,9 y., women — 1256 (69,9%), men — 540 (30,1%). In questionnaire module respondents analysed: 1) are there any cases of sudden death in family anamnesis at the age less than 45 y. and linked or suspicious to be linked to heart disease; 2) any complaints on palpitation; 3) presence of palpitations and their main characteristics; 4) episodes of TLC in anamnesis and their characteristics; and 14 questions more, than make it to suspect neuromediatory mechanism of TLC.Results. The prevalence of TLC in analysed population was 23%, maximum at the age of 40-49 y., reaching 28%. TLC were 2 times more prevalent in women than in men (27,5% and 13,5% resp., p<0,01). Median of the age of first episode was 16 (11; 23) y. o., taken that in 333 (<85%) respondents at the age <30 y. o. Almost in the half of cases (53% men, 46% women) the first TLC occurred at the age between 10 and 19 y. o., and with increasing of age probability of TLC decreased to the minimum of 1% in women of 60-69 y.o.The average length of anamnesis was 27,7 (12; 47) y. Most respondents (83,5%) had no any background somatic pathology. About the episodes of sudden death of immediate family members in younger age reported 27 persons (6,5%). Conclusion. In more than a half of patients, we found the signs showing a neuromediatory genesis of TLC (56%). These were the main cause for TLC in all age groups (50%-66%) as in men (60%) and women (55%). Th second cause was arrhythmic, having 6% of cases. In 35% the main cause for TLC by the method of questionnaire was not revealed.